MORAL VALUES ANALYSIS “Fight Club” - shofiyyah edwan mursalaat; tri budiarta (LIAISON JOURNAL OF BEST, 2023)
This study examines the moral principles present in David Fincher's movie Fight Club. The goals of this study are to categorize different moral principles and to outline the positive effects of those principles as they appear in the movie Fight Club. In this study, the author employs Creswell's (1994) descriptive qualitative methods, which make use of descriptive methodology to describe and analyze the data. The data is evaluated in a variety of methods, including identification, categorization, analysis, and conclusion-making. The author of this study utilized Linda and Eyre's (1997). The findings of this study include various types of moral values, including truthfulness, bravery, the capacity for peace, self-control, respect, kindness and friendliness, assurance, love and affection, fairness, and loyalty. The author also discusses the positive effects of moral principles on the main characters, as demonstrated in the movie Fight Club, where Jack and Tyler Durden have opposing moral principles. Bravery is the type of moral value that dominates the movie Fight Club. Keywords: Moral Value, Good impact, Fight Club